2022
DOI: 10.3389/fmolb.2022.977047
|View full text |Cite
|
Sign up to set email alerts
|

Multi-tissue metabolomic profiling reveals potential mechanisms of cocoon yield in silkworms (Bombyx mori) fed formula feed versus mulberry leaves

Abstract: Use of formula feed (FF) for silkworms for all instars, has promoted transformation and progress in traditional sericulture. However, the cocoon yield of FF silkworms has failed to reach that of silkworms fed mulberry leaves (ML). The biological mechanisms underlying this phenomenon have not been well described. This study aimed to identify metabolic mechanisms and potential biomarkers relating to the poor cocoon yield of FF silkworms. In this study, silkworms received treatments of either ML (ML group) or FF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Silk has been utilized in the textile industry for thousands of years due to its excellent physical and biological properties and is considered a potential material for biomedical applications (Huang et al 2018). The ability of silkworms to synthesize silk can be assessed by cocoon shell weight and cocoon shell rate, while the rate of inferior cocoons (such as double cocoons and deformed cocoons) can also affect silk production (Wu et al 2022). In this study, the cocoon quality of silkworms reared on artificial diets and mulberry leaves was investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silk has been utilized in the textile industry for thousands of years due to its excellent physical and biological properties and is considered a potential material for biomedical applications (Huang et al 2018). The ability of silkworms to synthesize silk can be assessed by cocoon shell weight and cocoon shell rate, while the rate of inferior cocoons (such as double cocoons and deformed cocoons) can also affect silk production (Wu et al 2022). In this study, the cocoon quality of silkworms reared on artificial diets and mulberry leaves was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Some silkworm varieties that are reared on artificial diets during all instars, such as Guican No. 5 (Zhang et al 2020), Zhong 2016 × Ri 2016 (Wu et al 2022), 5HT (A) (Nair et al 2011), have been successfully cultivated. However, silkworms raised on artificial diets have been reported to exhibit lower silk yield, lower cocoon shell rate (Shimura et al 2003, Tao et al 2022), and other issues, such as imbalanced amino acid ratios (Dong et al 2017, Tao et al 2022, Wu et al 2022), improved the amylase activity of digestive enzymes (Dai et al 2022), reduced DNA proliferation (Qin et al 2020), and susceptibility to infection with pathogens (Li et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…We also found a large amount of propyl gallate among the metabolites of the Malpighian tubules in silkworms reared on artificial diets. A previous study also showed the presence of propyl gallate in the metabolites of the intestine, hemolymph, and silk glands of silkworms fed artificial diets, which had a negative effect on silk production [ 57 ]. These results strongly suggest that propyl gallate is harmful to silkworms.…”
Section: Discussionmentioning
confidence: 99%
“…The silkworm larvae were fixed and cut in a dissecting pan with surgical nippers and scissors. The Malpighian tubules were collected on ice from the larvae on day 3 of the fifth instar, as this is the most active developmental stage for the silkworm [ 57 ]. The samples were rapidly frozen in liquid nitrogen and stored at –80 °C for subsequent transcriptomic and metabolomic profiling analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Dong et al [ 20 ] compared the metabolomic differences in hemolymphs between full-grown artificial feed-fed and mulberry leaf-fed silkworms and found differences in the metabolism of glycine, carbohydrates, etc., which may be related to the efficiency of silk protein synthesis. Most of the current studies on the differences between artificial diet feeding and mulberry leaf feeding in Bombyx mori have focused on growth and development [ 21 , 22 , 23 ] and nutrient uptake metabolism [ 24 , 25 , 26 ]. The exploration of the secondary structure and properties of silk from silkworms fed factory all-age artificial diets has not been reported.…”
Section: Introductionmentioning
confidence: 99%